Haemoglobin, magnetic resonance imaging markers and cognition: A subsample of population-based study 11 Medical and Health Sciences 1109 Neurosciences 11 Medical and Health Sciences 1103 Clinical Sciences - Tan, B. (BioMed Central Ltd., 2020)
10.1186/s13195-018-0440-5